Digital Inclusion in Older Adults: A Comparison Between Face-to-Face and Blended Digital Literacy Workshops - Martínez-Alcalá, Claudia I.; Rosales-Lagarde, Alejandra; Alonso-Lavernia, María de los Ángeles; Ramírez-Salvador, José Á.; Jiménez-Rodríguez, Brenda; Cepeda-Rebollar, Rosario M.; López-Noguerola, José Sócrates; Bautista-Díaz, María Leticia; Agis-Juárez, Raúl Azael (Frontiers in ICT, 2018)
As information and services are becoming more and more decentralized and they are often available in the cloud, an increasing number of older adults are expected to use Internet-based services –health, education, finance and others. For this reason, it seems important to plan models and/or strategies to allow the older adult population to acquire and enhance digital competencies more easily. The goal of this research is to show a blended workshop based on a Learning Management System (LMS) as a supporting tool for older adults’ digital literacy. This blended workshop was based on the adoption of an instructional model and on prior experiences of the groups of elderly that participated in the face-to-face workshops. This study involved 98 adults aged 60 and above, 72 Females (68.5 ± 6.9) and 26 Males (73.3 ± 7.4). 61 older adults participated in the face-to-face workshop (FFG) on digital literacy and 37 participated in the blended workshop (BLG). Digital literacy increased at the post-evaluation after the workshops but even more for the BLG. Likewise, in the validation of the blended workshop the results were positive regarding ease of use, perceived usefulness, attitude toward using and intention to use, which showed that older adults believe that it is useful to implement this type of supporting systems for developing their digital competencies. Hence, it is possible to conclude that older adults are capable of learning and acquiring digital literacy skills as long as they are strongly motivated or they know the functional benefits related to ICT.